2019
DOI: 10.1002/humu.23740
|View full text |Cite
|
Sign up to set email alerts
|

Screening for rare epigenetic variations in autism and schizophrenia

Abstract: While many studies have led to the identification of rare sequence variants linked with susceptibility to autism and schizophrenia, the contribution of rare epigenetic variations (epivariations) in these disorders remains largely unexplored. Previously we presented evidence that epivariations occur relatively frequently in the human genome, and likely contribute to a subset of congenital and neurodevelopmental disorders through the disruption of dosage‐sensitive genes. Here we extend this approach, studying me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Other studies have shown a significant increase of de novo epivariations in individuals with congenital disorders compared to control subjects 10 and provided evidence that epivariations contribute to the mutational spectra underlying autism and schizophrenia. 11 Epivariations can be subdivided based on their apparent etiology. 12 Primary epivariations are thought to be caused by stochastic errors in the establishment or maintenance of the epigenome, such as certain types of imprinting anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown a significant increase of de novo epivariations in individuals with congenital disorders compared to control subjects 10 and provided evidence that epivariations contribute to the mutational spectra underlying autism and schizophrenia. 11 Epivariations can be subdivided based on their apparent etiology. 12 Primary epivariations are thought to be caused by stochastic errors in the establishment or maintenance of the epigenome, such as certain types of imprinting anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we have shown that hypermethylated promoter epivariations are often associated with monoallelic expression, and thus can have an impact comparable to that of loss-of-function coding mutations 10 . Based on this observation, we anticipate that epigenetic profiling in patients with overt genetic disease, but who lack pathogenic sequence mutations in the gene(s) relevant to their phenotype, will lead to the identification of epivariants as a causative factor in some conditions, and potentially providing additional diagnostic yield compared to purely sequence based approaches 11 .…”
Section: Discussionmentioning
confidence: 99%
“…We then removed outlier samples, defined as those that showed cellular fractions either ≥99 th percentile +2%, or ≤1 st percentile -2% of any cell type. After these quality control steps, 23,173 samples remained for further processing and normalization, as described previously 10,11 . Briefly, raw signal intensities were subjected to color correction, background correction and quantile normalization using the Lumi package in R 22 , and the normalized intensities converted into β-values, which range between 0-1, representing the methylation ratio at each measured CpG.…”
Section: Quality Control and Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…These phenomena are not specific to ASD but may also be important in other disorders or phenotypes grouped under NDDs, including ID 29 . The incomplete penetrance and variable expressivity of ASD in the presence of a high-impact genetic variant may be under the influence of additional genetic variation [74][75][76] , including common genetic variation 7 or epigenetic factors [77][78][79] and possibly environmental contributions 80 . A polygenic risk score, which expresses the cumulative impact of thousands of common variants on the probability of a phenotypic outcome, for ASD explains approximately 2.5% of the observed variance 81 and has therefore no clinical use as a risk prediction tool in the general population at this time.…”
Section: Genetic Complexity Of Asdmentioning
confidence: 99%